Comprehensive Analysis of Potential ceRNA Network and Different Degrees of Immune Cell Infiltration in Acute Respiratory Distress Syndrome - Hu, Jiaxin; Ge, Shanhui; Sun, Borui; Ren, Jianwei; Xie, Jiang; Zhu, Guangfa (Frontiers in Genetics, 2022)
Abstract: Acute respiratory distress syndrome (ARDS) is a leading cause of death in critically ill patients. The specific mechanism of ARDS has not been fully elucidated. The aim of our study is to investigate the potential mechanism of ARDS, that is competing endogenous RNA (ceRNA) triple regulatory network, and evaluate immune cell infiltration patterns in patients. In this study, three microarray datasets that included 79 patients with sepsis-induced ARDS and 60 samples from sepsis alone patients were downloaded from the GEO public database, and differentially expressed genes (DEGs, including DElncRNAs, DEmiRNAs, DEmRNAs) were recognized by R software, followed by the GO and KEGG analysis and PPI network. We constructed a ceRNA network that contained 5 DElncRNAs, 7 DEmiRNAs and 71 DEmRNAs. Finally, we identified the TUG1/miR-140-5p/NFE2L2 pathway as the hub pathway in the whole network through correalation analysis and cytoHubba calculation in cytoscape. In addition, we also evaluate the distribution of 22 types of immune cells and identify three differentially expressed immune cells in sepsis-induced ARDS patients, that is B cells naïve, T regulatory cells (Tregs) and eosinophils. The correlation between immune cells and hub genes in ceRNA network was also evaluated. In conclusion, we demonstrated a new potential regulatory mechanism of the ARDS, that is TUG1/miR-140-5p/NFE2L2 ceRNA regulatory pathway, and may help us to further explore the molecular mechanisms underlying ARDS.